2006
DOI: 10.1177/230949900601400207
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Acute Achilles Tendon Rupture Using a Double-Ended Needle

Abstract: This double-ended needle repair technique is simple and reproducible. The needle is easy to make using a standard mini Steinmann pin with minimal cost. Combined with appropriate rehabilitation, the technique achieves good results and is associated with a low morbidity and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Those studies revealed no significant difference in the number of patients who returned to functional activities, in the ability to perform activities of daily living, or in patient satisfaction. There was also no difference in rerupture rate compared with open repair 65,66 . However, patients treated with the percutaneous technique had a lower incidence of wound breakdown or healing complications 65 .…”
Section: Treatment Of An Acute Rupturementioning
confidence: 72%
See 2 more Smart Citations
“…Those studies revealed no significant difference in the number of patients who returned to functional activities, in the ability to perform activities of daily living, or in patient satisfaction. There was also no difference in rerupture rate compared with open repair 65,66 . However, patients treated with the percutaneous technique had a lower incidence of wound breakdown or healing complications 65 .…”
Section: Treatment Of An Acute Rupturementioning
confidence: 72%
“…A multilayer closure helps to reduce skin tension and helps to prevent the formation of postoperative tendon adhesions to skin. 65,66 . Those studies revealed no significant difference in the number of patients who returned to functional activities, in the ability to perform activities of daily living, or in patient satisfaction.…”
Section: Treatment Of An Acute Rupturementioning
confidence: 98%
See 1 more Smart Citation
“…Two Level II studies have compared percutaneous repair with open repair. 32,46 These studies were unable to show any difference in return to sport or activities of daily living or in patient satisfaction. The percutaneous repair technique did not have a significantly different rerupture compared with open repair.…”
Section: Operative Treatmentmentioning
confidence: 97%
“…Operations with limited incisions to the tendon are less likely to cause arterial disruption if guided by the findings of this study. Percutaneous tenotomy has shown to be very successful, particularly in terms of healing and complication rates, which might be due to the conservation of the paratenon and deep fascia (Majewski et al, 2006;Ng et al, 2006). If incision to the deep fascia and paratenon is unavoidable, a posterior longitudinal incision, based on the median line, is most desirable as it will cause the least amount of vascular disruption.…”
Section: Implications For Surgical Approachesmentioning
confidence: 98%